2019
DOI: 10.12659/msm.918951
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dimethyl Fumarate on Atherosclerosis in the Apolipoprotein E-Deficient Mouse Model with Streptozotocin-Induced Hyperglycemia Mediated By the Nuclear Factor Erythroid 2-Related Factor 2/Antioxidant Response Element (Nrf2/ARE) Signaling Pathway

Abstract: BackgroundThis study aimed to investigate the effects of dimethyl fumarate (DMF) on thoracic aortic atherosclerosis in the apolipoprotein E (apo-E)-deficient mouse model with streptozotocin (STZ)-induced hyperglycemia, and the signaling pathways involved.Material/MethodsEight-week-old ApoE−/− male mice (n=30) were randomly divided into three groups: the Control group (ApoE−/−) (n=10); the diabetic model (STZ) group (n=10); and the DMF-treated (25 mg/kg) diabetic model (DMF+STZ) group (n=10). The area of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Activation of Nrf2 has been found to modulate redox homeostasis, prevent, and/or treat a large number of chronic inflammatory diseases in animal models and/or humans including CVD (Pall & Levine, 2015). Study has shown that the reduction of AS of the thoracic aorta has contributed to the activation of Nrf2 (Luo, Sun, Zhao, Tao, & Yan, 2019;Mimura & Itoh, 2015). HO-1 is a downstream protein of Nrf2; the increased expression of HO-1 is regulated by the activation of Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Nrf2 has been found to modulate redox homeostasis, prevent, and/or treat a large number of chronic inflammatory diseases in animal models and/or humans including CVD (Pall & Levine, 2015). Study has shown that the reduction of AS of the thoracic aorta has contributed to the activation of Nrf2 (Luo, Sun, Zhao, Tao, & Yan, 2019;Mimura & Itoh, 2015). HO-1 is a downstream protein of Nrf2; the increased expression of HO-1 is regulated by the activation of Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have also indicated its protective role in cardiomyocytes after I/R injury [ 157 ]. Additionally, in the apolipoprotein E (apo-E)-deficient mouse model with streptozotocin-induced hyperglycemia, DMF reduced the development of atherosclerosis [ 158 ].…”
Section: Therapies For Oxidative Stress-associated Cardiovascular mentioning
confidence: 99%
“…Activated Nrf2 is translocated into the nucleus to bind to ARE, through which it can activate the expression of downstream antioxidative genes (15). Accumulating evidence has also indicated that the activation of the Nrf2/ARE signaling pathway can increase antioxidative ability and reduce oxidative stress-induced injury to cells (11,(30)(31)(32).…”
Section: ' Discussionmentioning
confidence: 99%